2013
DOI: 10.1177/1471301213480157
|View full text |Cite
|
Sign up to set email alerts
|

‘Brightness in dark places’: Theatre as an arena for communicating life with dementia

Abstract: The aim of this study was to use artistic expressions on a theatrical stage for communicating life with dementia, as portrayed in literary texts and to explore whether such communication would help relatives of people suffering from dementia gain knowledge of their situation. Life with dementia was portrayed through four theatre performances with actors reading excerpts from literary texts combined with music. Relatives were invited to the performances and to participate in focus groups following the events. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…A burgeoning interest in creativity in the context of dementia has also manifested in a growing and diverse body of studies that have used innovative research methods to develop understandings of the subjective experience of living with dementia (e.g. Aadlandsvik, 2008; Bartlett, 2012; Buse & Twigg, 2016; Capstick & Ludwin, 2015; Gjengedal, Lykkeslet, S⊘rb⊘, & Sæther, 2014; Jenkins et al., 2016; Keady, Hydén, Johnson, & Swarbrick, 2017; Kontos, Miller, & Kontos, 2017). Examples of these include co-creational arts-based research methods such as poetry (Aadlandsvik, 2008), drama (Jenkins et al., 2016) and participatory film-making (Capstick & Ludwin, 2015), diary methods (Bartlett, 2012) and methods privileging material and embodied experience (Buse & Twigg, 2014, 2016, 2018; Kontos et al., 2017).…”
Section: Creative Methods Used To Study the Experience Of Dementiamentioning
confidence: 99%
“…A burgeoning interest in creativity in the context of dementia has also manifested in a growing and diverse body of studies that have used innovative research methods to develop understandings of the subjective experience of living with dementia (e.g. Aadlandsvik, 2008; Bartlett, 2012; Buse & Twigg, 2016; Capstick & Ludwin, 2015; Gjengedal, Lykkeslet, S⊘rb⊘, & Sæther, 2014; Jenkins et al., 2016; Keady, Hydén, Johnson, & Swarbrick, 2017; Kontos, Miller, & Kontos, 2017). Examples of these include co-creational arts-based research methods such as poetry (Aadlandsvik, 2008), drama (Jenkins et al., 2016) and participatory film-making (Capstick & Ludwin, 2015), diary methods (Bartlett, 2012) and methods privileging material and embodied experience (Buse & Twigg, 2014, 2016, 2018; Kontos et al., 2017).…”
Section: Creative Methods Used To Study the Experience Of Dementiamentioning
confidence: 99%
“…Previous research [11, 14, 15, 16] has focused mainly on educating health care workers, caretakers, and diagnosed patients. Those prior studies directly engaged with individuals involved in the dementia care process, and demonstrated an increase in understanding and caretaking approaches among their target audience.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the arts are effective at alleviating boundaries between service providers and people with dementia and in providing new insights for the dementia workforce and family members. The arts have a unique application for uncovering International Journal of Ageing and Later Life and communicating the interior worlds of those living with a dementia (Gjengedal et al 2014;Ryan et al 2009). The spate of recent theatre productions, memoirs, and films exploring various aspects of living with a dementia indicate that there is a receptive and wide audience for artistic contemplations of this condition.…”
Section: Discussionmentioning
confidence: 99%